A zero percent plastic ingestion rate by silver hake (Merluccius bilinearis) from the south coast of Newfoundland, Canada. (June 2018) - Liboiron, France; Ammendolia, Justine; Saturno, Jacquelyn; Melvin, Jessica; Zahara, Alex; Richárd, Natalie; Liboiron, Max
Abstract: Silver hake, ( Merluccius bilinearis ), contributes significant biomass to Northwest Atlantic ecosystems. The incidence of plastic ingestion for 134 individuals collected from Newfoundland, Canada was examined through visual examination of gastrointestinal contents and Raman spectrometry. We found a frequency of occurrence of ingestion of 0%. Through a comprehensive literature review of globally published fish ingestion studies, we found our value to be consistent with 41% ( n  = 100) of all reported fish ingestion rates. We could not statistically compare silver hake results to other species due to low sample sizes in other studies (less than n  = 20) and a lack of standardized sampling methods. We recommend that further studies should 1) continue to report 0% plastic ingestion rates and 2) should describe location and species-specific traits that may contribute to 0% ingestion rates, particularly in locations where fish consumption has cultural and economic significance. Highlights: Frequency of occurrence of plastic ingestion is 0% for silver hake ( n  = 134). First recorded baseline for silver hake plastic ingestion. Findings of 0% plastic ingestion describe important fish-plastic interactions. 41% of all fish species in English-language published research have ingestion rates of 0%. Low species sample sizes are an issue in 66% ( n  = 160) of published articles.